EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) PADA MATERI PELUANG DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Faqihi, Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The objective of this research was to investigate the effect of the learning models on learning achievement viewed from learning style types of the students. The learning models compared were PBL, GI, and classical with scientific approach model. The type of the research was quasi-experimental research with 3x3 factorial design. The population of this research was the students in grade X1 higher Secondary School in Lombok East on academic year of  2014/2015. The size of the sample was 282 students, which was taken by using stratified cluster random sampling technique. The instruments used for data collection were learning style questionnaire and mathematics achievement test. The hypothesis test used unbalance two ways analysis of variance. The results of the research were as follows. (1) the problem based learning model (PBL) and the cooperative learning model of the  group investgation (GI) type with scientific approach result in equal learning achievement in mathematics, buth both problem based learning model (PBL) and the cooperative learning model of the group investgation (GI) type give better result in learning achievement in mathematics than the classical with scientific approach. (2) the student with the high, medium, and ow independent learning levels have equal learning achievement. (3) in each of the learning models, the high, medium, and, low independent learning levels, result in the equal learning achievement. (4) in each of the independent learning levels, the problem based learning model (PBL) and the cooperative learning model of the  group investgation (GI) type with scientific approach result in equal learning achievement in mathematics, buth both problem based learning model (PBL) and the cooperative learning model of the  group investgation (GI) type give better result in learning achievement in mathematics than the classical with scientific approach.